High performance crosslinked system based on reaction of benzoxazine with benzoxazole. Issue 11 (13th March 2014) - Zhang, Kan; Cai, Ruilong; Zhuang, Qixin; Liu, Xiaoyun; Yang, Guang; Han, Zhewen
Abstract : A new crosslinking reaction between benzoxazine and benzoxazole was discovered by investigating the heat‐curing reaction of bisphenol A/aniline‐based benzoxazine monomer with a polybenzoxazole (PBO) model compound. This new crosslinking reaction provides a facile and straightforward method for the preparation of high‐performance crosslinked PBO/polybenzoxazine copolymer composites.